KESELAMATAN KONSTRUKSI: KONSEPSI DAN REGULASI - Endroyo, Bambang (Semarang State University, 2009)
Accident rate in Indonesia, specially at construction sector, was very bad. Therefore,seriuosly action for the minimization of construction accident must be done. In the year of 2009,Department of Public Work have theme: